Telesurgery in medical school and teaching hospital - Araújo-Filho, Irami; Rêgo, Amália Cínthia Meneses; Carvalho, Marília Daniela Ferreira; Melo, Luís Felipe Revorêdo Antunes; Galvão, Rafael Bessa Freitas; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2012)
Purpose: Telesurgery has been advertised for increasing efficiency, extending the scope of surgical practice, improving surgery outcomes, and reducing costs in the healthcare system. The aim of this article is to describe the some important aspects of telesurgery in medical schools, including the telecommunication requirements, the impact from lack of haptic feedback, surgeons adaptation, ethical and medicolegal issues. Methods: A review was done in Pubmed and ScieLo electronic platform, and a total of 20 representative articles were identified and are the basis of this review. Results: In this review we described the basic terms about telemedicine and telesurgery. We also described the guides for the establishment of telesurgical networks connecting various hospitals and centers in the world, allowing for rapid and safe dissemination of new surgical techniques. Telemedicine has been used to read image exams, interpret tests, consultation, conventional, laparoscopic and telerobotic surgery, manage diabetes, and manage postoperative follow up from remote sites. Reductions in time lost from work, transportation costs, more efficiency for the health care providers, and reducing medical costs all have been suggested as benefits of telemedicine. Conclusion: Despite the information published about telemedicine and telesurgery, this technology has been shown to be highly important in medical schools in rural hospitals, and war settings, with unequivocal benefits. Properly structured investigations will be needed to determine the role of telesurgery in the future.